ANALISIS KEBUTUHAN E-LKPD TERINTEGRASI PROBLEM BASED LEARNING DAN ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA - Utami, Herli Gusmita; Emiliannur, Emiliannur (Jurnal MIPA dan Pembelajarannya, 2025)
21st-century learning requires the younger generation to master critical thinking skills in order to face complex global challenges. However, at SMAN 1 Tebo, students' critical thinking skills are still low due to uninteresting teaching materials. Therefore, it is necessary to update teaching materials and learning models, such as E-LKPD based on Problem-Based Learning (PBL), which can increase students' active participation, deepen their understanding of physics concepts, and encourage analytical and problem-solving skills. The ethnoscience approach is also expected to integrate local wisdom to increase the relevance of physics materials to students' daily lives. This study aims to identify the need for teaching materials, assess students' critical thinking skills, and determine effective learning models to overcome them.